Donaugebiet (Bayern), Deutschland: Kastelle und Villen an Donau und Limes in Raetien: Forschungen zu römischen Militärund Zivilanlagen - Hüssen, Claus-Michael (e-Forschungsberichte des DAI, 2023)
The project on military and civilian places at the northern edge of the Roman Empire examines the creation and dissolution of frontiers, and considers the development of civilian settlements. By comparing different regions, regularities and variations may be indicated. The initial study area is the central area of the Raetian Limes. Areas for comparison are the eastern Dacian Limes in Romania and the middle Danube region. Prior to the 23rd International Congress of Roman Frontier Studies 2015 in Ingolstadt an excavation in Zandt on the Raetian Limes was carried out. Research on a smaller scale took place in the forts of Oberstimm and Ruffenhofen. Another area of activity was the communication of new research results to a wider audience.